Passion and purity : learning to bring your love life under Christ's control - Elliot, Elisabeth (Grand Rapids, Mich. : Fleming H. Revell, 2002)
Examines the relationships of men and women in accordance with God's laws and give direction in such areas as remaining sexually pure, knowing who and when to marry, and putting God's desires ahead of personal desires.
Me, Lord? Single? -- The life I owe -- Passion is a battleground -- Unruly affections -- Does God want everything? -- The snake's reasoning -- The first date -- Unfailing love -- The revelation -- Does God notice? -- Oozing ache -- Holding pattern -- Material for sacrifice -- Honor above passion -- Little deaths -- Life from deaths -- What to do with loneliness -- What providence has gone and done -- The rebel sigh -- Self-deception -- What woman do to men -- What do men look for? -- The mess we've made -- Hot sweats and wet feet -- Nobody knows the trouble -- A letter at last -- Whetted appetites -- How much can a kiss tell you? -- They abstain from nothing -- A "small" sin -- A cave and a driftwood fire -- How do you say no? Four bare legs -- His sublime keeping -- Impatience -- I have you now unravished -- Hold God to his bargain -- God granted and Go denied -- Confused rollings and wheels -- Love letters -- This is our God -We have waited for him -- Out of love into charity -- A new act of creation.
Includes bibliographical references (pages 189-191).
Keywords: Sex -- Religious aspects -- Christianity; Elliot, Elisabeth; Christian life